2006
DOI: 10.1158/0008-5472.can-05-2891
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine with β-Defensin 2–Transduced Leukemic Cells Activates Innate and Adaptive Immunity to Elicit Potent Antileukemia Responses

Abstract: Murine B-defensin 2 (MBD2) is a small antimicrobial peptide of the innate immune system. Recent study showed that MBD2 could not only recruit immature dendritic cells but also activate them by Toll-like receptor 4 and thus may provide a critical link between the innate immune system and the adaptive immune response. In this report, we examined the antileukemia activity of MBD2 in a murine model of acute lymphoid leukemia (ALL) L1210. L1210 cells were engineered to secrete biologically functional MBD2. MBD2-mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 44 publications
1
31
0
1
Order By: Relevance
“…Several alarmins have been reported to have the capacity to enhance antitumor immunity. Mouse b-defensin 2 can promote the generation of antitumor immunity against leukemia and melanoma through activation of DCs, T cell, and NK cells (12,29,34). HSPs are also reported to be capable of promoting antitumor CD8 responses (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Several alarmins have been reported to have the capacity to enhance antitumor immunity. Mouse b-defensin 2 can promote the generation of antitumor immunity against leukemia and melanoma through activation of DCs, T cell, and NK cells (12,29,34). HSPs are also reported to be capable of promoting antitumor CD8 responses (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also found that inoculation of mice with L1210-MBD2 induced augmented interleukin-12 (IL-12) and interferon-g (IFN-g) production. 3 These findings suggest that MBD2 acts as a critical link between the innate immune system and the adaptive immune response.…”
Section: Introductionmentioning
confidence: 91%
“…They modulate the cytokine response of mononuclear blood cells [11], and promote systemic antigen-or tumor-specific immune responses [12][13][14][15]. In keeping with these findings, human b-defensin (HBD)-1 to -3 as well as murine b-defensin (mBD)-2, -3 and -29 were shown to selectively chemoattract memory T lymphocytes and/or immature DC via CCR6 [12, [16][17][18].…”
Section: Introductionmentioning
confidence: 99%